Program Olahraga Nonprestasi untuk Meningkatkan Sumber Daya Mahasiswa - M. Sajoto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Non-Achievement Sports Program to Improve Students Quality. Our college students should be the ones who are productive, i.e. academically potential and physically and mentally healthy, in order that they can compete in this globalization era. Many efforts should be made to improve learners' physical fitness. One of them can be in the form of non-achievement sports program called sports for all. This program needs to be implemented continously at all department of universities throughout Indonesia.